Assessment of Soil Quality based on Relationship of Soil Carbon Stocks with Different Soil Parameters in Lakkampura Mini-watershed in Davanagere under Semi-arid Alfisols in India - L. Madhu, A. Sathish* and (Journal of the Indian Society of Soil Science, 2022)
A study was conducted in Lakkampura mini-watershed of Davanagere in Karnataka under semi-arid Alfisols to assess the soil quality. Two sets of soil samples were collected i.e. grid-wise surface soil samples for soil properties and depth wise samples at 0-15, 15-30, 30-45 and 45-60 cm in different land use/land covers. Analytical results of soil samples indicated soil pH from 5.3 to 7.8, EC of 0.10 to 0.18 dS m-1, organic carbon of 4.8 to 7.5 g kg-1, available N of 262.5 to 450.8 kg ha-1, available P 7.02 to 11.20 kg ha-1, available K 145.1 to 219.0 kg ha-1. At 0-15 cm, soil carbon stocks (SCS) ranged from 8.10-15.26 t ha-1, at 15-30 cm, from 6.04-14.15 t ha-1, at 30-45 cm, SCS ranged from 3.51-11.34 t ha-1, at 45-60 cm, SCS ranged from 1.34-8.78 t ha-1 under four land use land covers potential for carbon stocks. The SCS collected in grid samples ranged from 6.43-13.66 t ha-1. Based on principal component analysis (PCA), six PCs (PC1, PC2, PC3, PC4, PC5 and PC6) were significant and explained 71.5% variability in parameters. The quality of the soil was assessed based on a soil quality index (SQI) by considering the significantly loaded soil parameters on PCs. The mean contribution of soil parameters to SQI ranged from 0.026 (P) to 0.274 (bulk density). The bulk density had minimum CV, while electrical conductivity had maximum CV in the contribution to SQI.